2023
DOI: 10.1002/ece3.10003
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized diversity, genetic structuring, and phylogeography of the genus Triplophysa (Cypriniformes: Nemacheilidae) sheds light on two opposite colonization routes during Quaternary glaciation that occurred in the Qilian Mountains

Abstract: In recent years, the influence of historical geological and climatic events on the evolution of flora and fauna in the Tibetan Plateau has been a hot research topic. The Qilian Mountain region is one of the most important sources of biodiversity on the Qinghai-Tibet Plateau. Many species existed in the region during the Pleistocene glacial oscillation, and the complex geographical environment provided suitable conditions for the survival of local species. The shrinkage, expansion, and transfer of the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…In the divergence-time analysis, these three clades were estimated to diverged 7–10 Ma. The divergence is relatively deep compared to the intraspecies differentiation in other Triplophysa species ( Hu et al 2020 , 2022 ; Wu et al 2020 ; Du et al 2023 ), suggesting they might be divided into several potential subspecies, or even species, which need extra analyses including morphology and phylogeny with more samples. These results offer insights into the evolutionary history of T. dalaica , as well as the correlation between the change of population and historical climate and geological events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the divergence-time analysis, these three clades were estimated to diverged 7–10 Ma. The divergence is relatively deep compared to the intraspecies differentiation in other Triplophysa species ( Hu et al 2020 , 2022 ; Wu et al 2020 ; Du et al 2023 ), suggesting they might be divided into several potential subspecies, or even species, which need extra analyses including morphology and phylogeny with more samples. These results offer insights into the evolutionary history of T. dalaica , as well as the correlation between the change of population and historical climate and geological events.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their widespread distribution, species of Triplophysa exhibit adaptability to diverse habitats, including cold environments, hypoxia, and saline waters. In recent years, multiple aspects including the phylogenetic relationships among Triplophysa species ( Wang et al 2016 , 2023 ; Chen et al 2019 ; Wu et al 2020 ), phylogeography ( Hu et al 2020 , 2022 ; Zhong et al 2022 ; Du et al 2023 ), patterns of population differentiation ( Zhou et al 2021b ; Jin et al 2022 ), and the adaptations to various habitats ( Chen et al 2020b , 2020a ; Zhang et al 2023 ) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that ancient climate and geological events might be important factors affecting the current geographical distribution and genetic differentiation of species in the Qinghai-Tibet Plateau [ 58 61 ]. In this study, the effective population of S. o’connori decreased for a short time in the late accelerated uplift stage of the Qinghai Tibet Plateau (~ 1 million years ago) and the Quaternary Ice Age [ 24 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%